Pengaruh kesegaran jasmani dan motivasi belajar terhadap hasil belajar pendidikan jasmani, olahraga, dan kesehatan - Masrun Masrun; Iyakrus Iyakrus; Dian Pujianto (Altius: Jurnal Ilmu Olahraga dan Kesehatan, 2022)
The purpose of this study is to find out the influence of Physical Fitness and Learning Motivation on Physical Education Learning Achievement. Based on the research goals, this study used quantitative (associative) multiple linear regression methods. This study was conducted in SMPN 18 Padang. The population was the student of class 17, who participated in an extracurricular program.   The sample was taken by total sampling technique and with a total of 39 students. Physical Fitness was measured by the TKJI test, Learning Motivation was measured by a questionnaire, and Physical Education Achievement was taken from the test result of Physical Education Learning Achievement of the semester II periods. Before processing the data, several tests were made in advance, which was: the normality residual test, multicollinearity test, heteroscedasticity test, and autocorrelation test. The results of data analysis show that: (1) Physical Fitness influence Physical Education Learning Achievement (sig 0.00<0.05). (2) Leaning Motivation influence toward Physical Education Learning Achievement (sig 0.04 <0.05). (3) Physical Fitness and Leaning Motivation simultaneously affect Physical education Learning Achievement (sig 0.00 <0.05).